COMPARISON OF OCCLUSAL VERTICAL DIMENSION USING ANALYSIS OF SEVERAL VERSIONS OF DIGITAL PHOTO SOFTWARES - Rani Purba; Feby Kuntum; Puput Rizkika; Sri W. Rais; Arya Prasetya Beumaputra (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Digital photo analysis is an alternative method of measuring the vertical dimension occlusion (OVD) in the denture processing by using graphic design softwares such as bitmap and vector-based software. The 2020 version of bitmap software has advantages such as online data storage, and upsampling feature that is used to improve image quality as well as the 2020 version of vector software. This study aimed to compare the results of OVD measurements using the analysis of several versions of digital photo softwares and direct measurements (Willis method). Methods: This study was an analytic observational study with a cross-sectional approach. The total sample in this study was 30 students of the Sriwijaya University Dentistry Study Program from previous studies, divided into 5 groups; group I Willis method, group II 2012 version of bitmap, group III 2012 version of vector, group IV 2020 version of bitmap, group V 2020 version of vector software. The OVD was measured from subnation to menton in occlusion using the Willis method and several digital photo software analysis methods. The data were tested using one-way ANOVA test. Results: The results of the one-way ANOVA test showed OVD differences of the direct method and digital photo software methods were not significant (p>0.05). Conclusion: There was no difference in the results of the occlusal vertical dimension between the groups.